2009
DOI: 10.2337/diaspect.22.1.56
|View full text |Cite
|
Sign up to set email alerts
|

The Carbohydrate Counting in Adolescents With Type 1 Diabetes (CCAT)Study

Abstract: Feature Article / Carbohydrate Counting in Adolescents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 15 publications
5
79
2
2
Order By: Relevance
“…4 Another obstacle is lack of competency in carbohydrate counting; several studies have shown that inaccuracy in carbohydrate counting is widespread among children and adults. 3,[5][6][7] Because these dosage calculations can be both complex and time-consuming, individuals often rely on empirical estimates of their insulin needs, which can limit their ability to achieve optimal glycemic control. 8 Many current insulin pump systems feature bolus advisor capability, which automatically calculates insulin boluses to address carbohydrate intake and out-of-range BG levels.…”
mentioning
confidence: 99%
“…4 Another obstacle is lack of competency in carbohydrate counting; several studies have shown that inaccuracy in carbohydrate counting is widespread among children and adults. 3,[5][6][7] Because these dosage calculations can be both complex and time-consuming, individuals often rely on empirical estimates of their insulin needs, which can limit their ability to achieve optimal glycemic control. 8 Many current insulin pump systems feature bolus advisor capability, which automatically calculates insulin boluses to address carbohydrate intake and out-of-range BG levels.…”
mentioning
confidence: 99%
“…In a study with 2530 children and children with diabetes, 73 percent were within 10-15 grams of the actual carbohydrate amount. [80] However, a study by Bishop and colleagues [81] found that in their sample of 48 adolescents aged 12 to 18, most youth could not accurately count carbohydrates. However they found that children who did successfully count carbohydrates had significantly lower A1C levels.…”
Section: New Technology Influencing Adherence and Glycemic Controlmentioning
confidence: 99%
“…Diabetics have to attend courses on CHO counting based on empirical rules; however even well trained patients face difficulties, according to studies. [4][5][6] In Brazeau et al, 4 the average error in CHO counting by 50 T1D adults was 15.4 ± 7.8 grams, while in Bishop et al 5 only 11 of 48 adolescent T1D patients estimated daily CHO with an error less than 10 grams. In a study involving children with T1D and their caregivers, CHO estimations were inaccurate by at least ± 15 grams for 27% of the meals.…”
mentioning
confidence: 94%